2017
DOI: 10.12659/msm.899088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treatment with Twin-Block Appliances on Body Posture in Class II Malocclusion Subjects: A Prospective Clinical Study

Abstract: BackgroundThere is strong evidence that malocclusion and body posture are interdependent. The relationship between improvement of nasopharyngeal airway, correction of malocclusion by orthodontic treatment or orthognathic surgery, and changes in body posture were evaluated in several studies. The purpose of the present study was to analyze the effect of the orthodontic treatment with Twin-block appliance on body posture.Material/MethodsThe study group consisted of 23 children (mean age 12.45 (1.06) years). They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
3
0
4
Order By: Relevance
“…Por otra parte, estudios como el de González (14) y Smailiené (17) no lograron resultados estadísticamente significativos para demostrar una correlación entre las variables estudiadas. González, tras un estudio descriptivo transversal en 19 niños, de 7 a 12 años de edad, con maloclusiones clase II y III de Angle y realizado a través de examen bucal y telerradiografía, presentó resultados predominantes de clase II, ángulo cráneo-vertebral y espacio suboccipital dentro del rango normal.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Por otra parte, estudios como el de González (14) y Smailiené (17) no lograron resultados estadísticamente significativos para demostrar una correlación entre las variables estudiadas. González, tras un estudio descriptivo transversal en 19 niños, de 7 a 12 años de edad, con maloclusiones clase II y III de Angle y realizado a través de examen bucal y telerradiografía, presentó resultados predominantes de clase II, ángulo cráneo-vertebral y espacio suboccipital dentro del rango normal.…”
Section: Discussionunclassified
“…La Tabla 3 muestra los estudios que no encontraron asociación entre PCC y maloclusiones, donde se incluyeron tres estudios (14,17,22) .…”
Section: No Asociación De Las Alteraciones De La Pcc Y Las Maloclusionesunclassified
See 1 more Smart Citation
“…Respecto a la modificación de la postura ocasionada por el uso de dispositivos ortopédicos/ ortodónticos se ha reportado con anterioridad (Smailiene et al, 2017) que la terapéutica a través de Twin-block tras 10 a 14 meses de uso reduce significativamente la presencia de cifosis, lordosis, ángulos cervicales y torácicos y pelvis, de forma similar a la observada en el presente estudio, sin embargo los cambios observados no son atribuidos por los investigadores a uso del dispositivo, si no al mero crecimiento corporal fisiológico. Al respecto nos es posible argumentar que la E1 refleja un efecto inmediato y la E2 la permanencia durante el periodo de uso, por lo que podemos asumir que los cambios observados son ocasionados por el AOF.…”
Section: Discussionunclassified
“…A survey of the pertinent literature showed many studies that have reported effects of the TB with the use of routine skeletal and dental landmarks, but none reporting the effects of the TB on cervical posture. 18,19 The objective of the present study was to compare the cervical spine posture between subjects with and without TB therapy. The null hypothesis was that no differences are observed in the cervical spine posture between the 2 groups.…”
mentioning
confidence: 99%